1978
DOI: 10.1007/bf00415721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on diauxic growth with glucose and organic acids in Pseudomonas fluorescens

Abstract: Growth of Pseudomonas fluorescens in batch culture with glucose and organic acids resulted in typical diauxic responses at 30 degrees C but no detectable diauxic lag at 5 degrees C. At 30 degrees C, organic acids were preferentially utilized during the first growth phase. Glucose utilization was delayed until onset of the second growth phase. Systems involved in direct uptake and catabolism of glucose responded in a manner compatible with repression by malate and/or its metabolites and induction by glucose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Whatever its mechanism, it is likely that the same catabolite repression control system exists in the fluorescent pseudomonads, since we were able to identify proteins which were antigenically similar to Crc in P. putida and P. fluorescens but not in E. coli. The existence of a common mechanism of catabolite repression control in these closely related species is not surprising, since repression by organic acids has been observed in all three species (16,42).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whatever its mechanism, it is likely that the same catabolite repression control system exists in the fluorescent pseudomonads, since we were able to identify proteins which were antigenically similar to Crc in P. putida and P. fluorescens but not in E. coli. The existence of a common mechanism of catabolite repression control in these closely related species is not surprising, since repression by organic acids has been observed in all three species (16,42).…”
Section: Discussionmentioning
confidence: 93%
“…Bacterial strains and plasmids used in this study are listed in Table 1. P. aeruginosa was grown at 37ЊC in basal salts medium (BSM) (16) or in Luria-Bertani (LB) medium (22). Pseudomonas fluorescens and P. putida were grown at 30ЊC in LB medium.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies with different bacterial species showed that occurrence of diauxic growth behavior critically depends on the history of the inoculum (5,9,11). Therefore, batch cultures were first inoculated with cells pregrown with acetate.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, enzymes involved in the metabolism of the less preferred substrate occur after exhaustion of the preferred substrate (1,4,5,7,9,11). However, if the inoculum is grown on the less favored substrate, the lag between the two phases of diauxic growth becomes obscured.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the lag is significantly reduced with an inoculum prepared on mannopine. In some (10,17,20), although not all (26) figure. lag phase was similarly decreased with an inoculum prepared on the less preferred substrate.…”
Section: Materuils and Methodsmentioning
confidence: 97%